(untitled) (Eurasian Research Bulletin, 2023)
The article describes the necessary information about agriculture, plant protection, harmful insects, diseases, weeds, pesticides, organophosphorus compounds, humans and warm-blooded animals, rules of use, waiting period, biological efficiency, and environmental cleanliness.